1983
DOI: 10.1063/1.94100
|View full text |Cite
|
Sign up to set email alerts
|

Growth of hydrogenated amorphous silicon due to controlled ion bombardment from a pure silane plasma

Abstract: The growth process, optical and structural properties of a-Si:H films deposited from a silane multipole dc discharge are analyzed by real time and spectroscopic ellipsometry, and ir absorption spectroscopy. Films deposited mainly from neutral polymerized species are systematically compared to films deposited from monomeric ionic species at various ion incident energy up to 100-eV. An increase of ion bombardment energy is shown to favor the formation of high density homogeneous and isotropic films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
3

Year Published

1985
1985
2009
2009

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(27 citation statements)
references
References 11 publications
1
23
0
3
Order By: Relevance
“…These results imply that the vacancy incorporation increases with increasing ionbombardment energy. The same trend has been observed for a-Si: H deposition using different deposition techniques, 7,12 demonstrating the generality of the ion-surface interactions which affect the vacancy incorporation.…”
Section: B the Relation Between The Microstructure And The Additionasupporting
confidence: 54%
See 2 more Smart Citations
“…These results imply that the vacancy incorporation increases with increasing ionbombardment energy. The same trend has been observed for a-Si: H deposition using different deposition techniques, 7,12 demonstrating the generality of the ion-surface interactions which affect the vacancy incorporation.…”
Section: B the Relation Between The Microstructure And The Additionasupporting
confidence: 54%
“…In general the deposition conditions with ion bombardment result in denser a-Si: H films as demonstrated for dc discharges, rf-plasma enhanced chemical vapor deposition ͑rf-PECVD͒, very high frequency PECVD ͑VHF-PECVD͒, and electron cyclotron resonance CVD ͑ECR-CVD͒ with substrate bias. [7][8][9][10] Hamers et al 9 showed that good structural properties ͑a minimum incorporation of nanosized voids͒ can be obtained when the ions deliver an energy higher than 5 eV per deposited Si atom in a VHF-PECVD silane plasma. This result implies that significant film growth modification by ions depends on the typical binding energies of the Si-Si and Si-H bonds in the a-Si: H, which are both around 3 eV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The size distribution of ions depends on substrateto-cathode distance d 8 c [12] and the MS result shows higher monosilicon ions for smaller d.c· The substrate temperature of 240°C, 0.5 m torr pressure was used. By reducing the pressure to less than 0.5 m torr, the ionic species, mainly SiHt and SiH~ can be made dominant [13,14] which provide for higher optical band-gap, but results in columnar microstructures. The ion-molecule reaction is one of the gas phase reactions.…”
Section: Plasma Deposiuon Mechal'ismmentioning
confidence: 99%
“…To reach this goal we produced hydrogenated diphasic nanostructured silicon thin films close to the onset of dusty plasma conditions, within the amorphous to microcrystalline transition region, using high hydrogen dilution conditions [32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%